A Case Study on the Development of Adult Language, Literacy and Numeracy Skills - Ahmed, Mohiuddin (EAI Endorsed Transactions on e-Learning, 2019)
Language, literacy and numeracy (LLN) are integral part of our lives, especially in workplace. In this paper, the current research on adult LLN practices are investigated. A case study based on a group of students’ LLN scores are presented in this paper. The scores are analysed and appropriate support strategies are proposed to achieve the expected level of LLN for their qualification. There is a significant lack of research and methods to improve the LLN scores in the vocational sector to match the desired level of qualification and hence a case study in this area can be used as a reference. Additionally, the proposed approaches are purely based on classroom teaching and hence leaves a footprint to investigate further to identify ways to formalize these approaches. This contributions made in this paper will be helpful for academics and teaching staffs in the adult education sector. This paper can be used as a general reference for any qualification in the vocational education sector.
Keywords: Adult Education; LLN; Vocational Education